Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822) - Ng, Heok Hee (Zootaxa, 2005)
Glyptothorax botius is revalidated from synonymy with G. telchitta. Both G. botius and G. telchitta are known from the Ganges River drainage in northeast India, and differ from congeners in the region in having a combination of large, prominent tubercles on the head and body, a thoracic adhesive apparatus without a median depression, and a very slender body and caudal peduncle. Glyptothorax botius was previously considered a synonym of G. telchitta, but differs from it in having a more rounded snout when viewed laterally, the presence (vs. absence) of dark saddles on the body, a thoracic adhesive apparatus with broader folds of skin, a longer adipose-fin base (12.0–16.4% SL vs. 9.5–11.5) and a more slender caudal peduncle (3.1–4.2% SL vs. 4.7–5.9). Both species are redescribed in this study, and neotypes are designated to fix their taxonomy.